An Investigation Model Aimed at Combating Server-based Gaming, Illicit Online Gaming, and Computer Gaming Delinquency in South Africa - Philly Masogo; John Motsamai Modise (Current Progress in Arts and Social Studies Research Vol. 10, 2025)
The chapter’s goal is to create a thorough investigation methodology that will counteract server-based gaming, illicit internet gaming, and computer gaming delinquency in South Africa. This study develops an investigation model aimed at combating these issues by integrating legal, technological, and social frameworks. The model is designed to identify, monitor, and address various forms of gaming delinquency, including underage gaming, addiction, and illegal gambling operations. Through a comprehensive analysis of existing literature, case studies, and current regulatory practices, the model proposes a multifaceted approach that involves collaboration between law enforcement agencies, gaming companies, and regulatory bodies. Principal arguments. The cross-border nature of the inquiry, technological improvements, and cultural issues pose substantial problems, and the investigation model should include intelligence collecting, technical investigation, legal enforcement, and prevention activities. International collaboration, specialized methods, robust legal frameworks, and public awareness are necessary for effective addressing. Methodological approach: Review of the literature on current studies and recommended procedures, examination of pertinent laws and rules, conversations with authorities on gaming and cybercrime, and evaluation of South Africa’s present situation regarding computer game delinquency. Significance/Implications: The suggested investigation approach can help create efficient preventive and treatment initiatives, and it can act as a guide for South African lawmakers and law enforcement organizations in their efforts to counteract the negative impacts of computer game delinquency. The findings suggest that implementing this model could significantly reduce illegal gaming activities and promote a safer, more controlled gaming environment in South Africa. The study concludes with recommendations for policymakers and stakeholders to enhance the effectiveness of gaming regulations and protect vulnerable populations from the negative impacts of gaming delinquency. International initiatives to solve comparable issues in other nations can benefit from the findings. Audience: Parents and guardians, researchers, legislators, law enforcement organizations, and gaming communities. In conclusion, by implementing a comprehensive investigation model and fostering international cooperation, stakeholders can significantly reduce the prevalence of illegal online gambling and create a safer online environment for all.